Classroom Learning Environment Differences Between Resilient, Average, and Nonresilient Middle School Students in Reading. (March 2014) - Padrón, Yolanda N.; Waxman, Hersh C.; Lee, Yuan-Hsuan
The lack of achievement of students from high-risk and high-poverty environments necessitates changes in today's middle school environments to create a caring, supportive environment where all middle school students can succeed. This study investigated the classroom learning environments of resilient, average, and nonresilient minority students in middle school reading classrooms. A total of 1, 295 seventh- and eighth-grade minority students were administered an adapted version of the My Class Inventory. The results revealed that resilient students had more positive perceptions of their reading class than average and nonresilient students. On the other hand, nonresilient students perceived their reading class to be more difficult and have more friction than average and resilient students. Further research is needed in this area that examines specific ways that teachers can improve the learning environments for nonresilient students without diminishing the more supportive learning environment that currently exists for other students in their classes.